How Does Search for Meaning Lead to Presence of Meaning for Korean Army Soldiers? The Mediating Roles of Leisure Crafting and Gratitude - Lim, Jung In; Yu, Jason; Sohn, Young Woo (Frontiers in Psychology, 2022)
Many studies demonstrate that finding meaning in life reduces stress and promotes physical and psychological well-being. However, extant literature focuses on meaning in life among the general population (e.g., college students or office workers) in their daily lives. Thus, this study aimed to investigate the mechanisms of how individuals living in life-threatening and stressful situations obtain meaning in life, by investigating the mediating roles of leisure crafting and gratitude. A total of 465 Army soldiers from the Republic of Korea (ROK) participated in two-wave surveys with a 2-week interval. Structural equation modeling analyses indicated that the direct effects between the search for meaning, presence of meaning, leisure crafting, and gratitude were significant, except for the direct relationship between the search for meaning and the presence of meaning, and between leisure crafting and the presence of meaning. We tested indirect effects using a Monte Carlo approach and found that leisure crafting and gratitude sequentially mediated the relationship between the search for meaning and the presence of meaning. Our findings highlight the importance of the motivation behind searching for meaning, the proactive use of leisure time, and gratitude for individuals in stressful situations and controlled lifestyles. Finally, we discuss the implications and limitations of this research and future research directions.